Risk of lung disease in the PI*SS genotype of alpha-1 antitrypsin: an EARCO research project - Martín, Teresa; Guimarães, Catarina; Esquinas, Cristina; Torres-Duran, Maria; Turner, Alice M; Tanash, Hanan; Rodríguez-García, Carlota; Corsico, Angelo; López-Campos, José Luis; Bartošovská, Eva; Stæhr Jensen, Jens-Ulrik; Hernández-Pérez, José María; et al. (Respiratory research, 2024)
BACKGROUND: The PI*S variant is one of the most prevalent mutations within alpha-1 antitrypsin deficiency (AATD). The risk of developing AATD-related lung disease in individuals with the PI*SS genotype is poorly defined despite its substantial prevalence. Our study aimed to characterize this genotype and its risk for lung disease and compare it with the PI*ZZ and PI*SZ genotypes using data from the European Alpha-1 antitrypsin Deficiency Research Collaboration international registry. METHOD: Demographic, clinical, functional, and quality of life (QoL) parameters were assessed to compare the PI*SS characteristics with the PI*SZ and PI*ZZ controls. A propensity score with 1:3 nearest-neighbour matching was performed for the most important confounding variables. RESULTS: The study included 1007 individuals, with PI*SS (n = 56; 5.6%), PI*ZZ (n = 578; 57.4%) and PI*SZ (n = 373; 37.0%). The PI*SS population consisted of 58.9% men, with a mean age of 59.2 years and a mean FEV1(% predicted) of 83.4%. Compared to PI*ZZ individuals they had less frequent lung disease (71.4% vs. 82.2%, p = 0.037), COPD (41.4% vs. 60%, p = 0.002), and emphysema (23.2% vs. 51.9%, p < 0.001) and better preserved lung function, fewer exacerbations, lower level of dyspnoea, and better QoL. In contrast, no significant differences were found in the prevalence of lung diseases between PI*SS and PI*SZ, or lung function parameters, exacerbations, dyspnoea, or QoL. CONCLUSIONS: We found that, as expected, the risk of lung disease associated with the PI*SS genotype is significantly lower compared with PI*ZZ, but does not differ from that observed in PI*SZ individuals, despite having higher serum AAT levels. TRIAL REGISTRATION: www. CLINICALTRIALS: gov (ID: NCT04180319).
Keywords: Registries; Humans; alfa-1-antitrypsin; Lung disease; alpha 1-Antitrypsin; lidé středního věku; registrace; Quality of Life; Alpha-1 antitrypsin; Female; rizikové faktory; Aged; senioři; lidé; plicní nemoci; Genotype; kvalita života; ženské pohlaví; Male; Middle Aged; Lung Diseases; deficit alfa1-antitrypsinu; genotyp; alpha 1-Antitrypsin Deficiency; PI*SS; mužské pohlaví; Risk Factors